Analysis of Generation Characteristics of Large-Scale Synchronous Generators for Hydroelectric Power - Kim, Chang-Woo; Jang, Gang-Hyeon; Shin, Kyung-Hun; Won Seo, Sung; Choi, Jang-Young (International Journal of Engineering and Technology, 2018)
Background/Objectives: Hydroelectric power generators are used in various capacities from small capacity to large capacity, but research on large capacity generators is lacking.Methods/Statistical analysis: The electromagnetic characteristics of 1MW class wound type synchronous generators are analyzed. No load analysis, load analysis, and operation characteristics analysis are performed.A commercial finite element method tool is used for the electromagnetic characteristics analysis. The reliability of the analysis is secured through the experiments.Findings:Electromagnetic characteristics of a 1MW class wounded type synchronous generators are analyzed by using finite element method. First, the power generation characteristics under rated conditions are analyzed. Next, open circuit analysis and short circuit analysis are performed to consider the saturation characteristics of the generator. In addition, the reliability of the analysis is secured through the experiments. Finally, the V-curve according to the capacity and power factor of the SG is extracted and the operation interval was secured accordingly. This can be interpreted the field currents in lagging power factor operation and leading power factor operation, and can check the thermal limiting period of the field windings generated during the leading power factor operation.Improvements/Applications:This paper can be used for analysis and design of large capacity wound type synchronous generator.Â Â Â